1994
DOI: 10.1161/01.cir.89.6.2498
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled nitric oxide as a marker for organic nitrate tolerance.

Abstract: Measurements of exhaled NO provide in vivo, noninvasive evidence for the development of biochemical tolerance to nitroglycerin. There was reduced NO release into exhaled gas from the pulmonary vasculature concomitant with evidence of tolerance to nitroglycerin vasodilation in the systemic circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“…43,44 Our study has extended these observations and suggests that monitoring GTN-induced exhaled NO could be used to assess primary and secondary nitrate tolerance in the clinical setting. 37 Although these observations clearly demonstrate pulmonary microvascular injury during lung transplantation, the exact molecular mechanisms, the implications to microvascular reactivity and endothelial permeability, and overall clinical relevance remain to be uncovered. Our working hypothesis is that increased oxidative stress is responsible for NO attenuation and the activity of NO pathways could be restored by appropriate anti-oxidant therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…43,44 Our study has extended these observations and suggests that monitoring GTN-induced exhaled NO could be used to assess primary and secondary nitrate tolerance in the clinical setting. 37 Although these observations clearly demonstrate pulmonary microvascular injury during lung transplantation, the exact molecular mechanisms, the implications to microvascular reactivity and endothelial permeability, and overall clinical relevance remain to be uncovered. Our working hypothesis is that increased oxidative stress is responsible for NO attenuation and the activity of NO pathways could be restored by appropriate anti-oxidant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…24,26 To further investigate the fate of NO pathways in the microvascular lung compartment, one can deliver exogenous NO to the pulmonary circulation and monitor evolution of this NO in exhaled breath. 18,23,[35][36][37] We have suggested that GTN-induced exhaled NO might be a useful tool to monitor metabolic function of the pulmonary microvasculature. This proposed test has numerous clinical, diagnostic and mechanistic advantages and could compliment the current clinical diagnostic efforts.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16] and suggested that exhaled NO during exercise can be a marker of spilled NO from the pulmonary vasculature. Another study demonstrated that the decrease in exhaled NO was associated with diminished vasodilation in a nitroglycerin tolerance test, 23 which supported a linkage of endothelium function with exhaled NO. Based on these observations, the present study hypothesized that exhaled NO output may be linked to impaired oxygen kinetics at the onset of exercise, caused by an insufficient increase in cardiac output in patients with CHF.…”
Section: Background and Hypothesismentioning
confidence: 91%
“…13 Exhaled NO levels have also been found to increase with exercise 14 and in response to orally administered L-arginine 15 and intravenously infused nitroglycerin. 16 Conversely, the exhaled NO level is decreased in patients with heart failure, 17 hypertension, 18 and acute respiratory distress syndrome. 19 The exhaled NO level is also reduced by smoking.…”
Section: Sumino Et Al Enalapril Increases Exhaled Nitric Oxidementioning
confidence: 99%